Analisa Kinerja Keuangan Bank BUMN dan Bank Swasta Berdasarkan Rasio Keuangan - Misral Misral; Sri Rahmayanti; Norra Isnasia Rahayu (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This final project discusses the comparison of the financial performance of state-owned banks and private banks based on financial ratios in the 2015-2019 period. The financial ratios used consist of CAR, NPL, NIM, BOPO, ROA, ROE, and LDR. The data used in this study were obtained from published financial reports for 2015 to 2019 published by the respective banks. After passing the purposive sample stage, 4 state-owned banks and 9 private banks were obtained as samples in this study. The results of this study explain that there are differences in the financial performance of state-owned banks and private banks as measured by financial ratios. State-owned banks have better performance in terms of ROE, ROA, CAR ratios, while private banks have better performance in terms of NPL, BOPO, LDR ratios.